BUILD A MODEL OF THE TRANSPORT NETWORK OF CHERNIHIV REGION WITH THE HELP OF GIS TECHNOLOGIES - Зацерковний, В. І.; Тішаєв, І. В.; Кобрін, О. В. (Science-based technologies, 2016)
The problem of road congestion (transport networks) can be solved in two ways - by increasing the size of the actual transport network (increase in the number of traffic lanes, construction of new roads, road bridges, interchanges, etc.) or by improving traffic management process.Improve the efficiency of transport networks is possible with the help of information technology, particularly geographic information technology. Traditional mapping of highways performed when surveying the area in order to create or update the first topographic maps to scale. Transport model is a program consisting of information and settlement units. On the basis of ArcGIS technology manages the sphere of transport of hundreds of cities and regions throughout the world. According to the GDF standard, depending on the granularity of data presentation on the main road elements of road infrastructure data model are considered at three levels. Model nodes logically linked data allowed maneuvers (turns, reversals or their prohibition, etc.).